Optimalisasi Pembelajaran melalui Pemutakhiran Rencana Pembelajaran Semester (RPS) dan Penyusunan Rancangan Bahan Ajar Mata Kuliah Teknik Penyambungan Digital - Riesa Krisna Astuti Sakir (KOLONI, 2022)
This research aims to optimize the learning of the Digital Connection Engineering course in the Undergraduate Study Program in Applied Telecommunication Network Engineering Technology, Department of Electrical Engineering, Ujung Pandang State Polytechnic by adapting the independent learning curriculum. Using the fishbone diagram method, the problem is described to find the root of the problem and design the required solution. There are three solutions designed, including updating the Semester Learning Plan (RPS), preparing teaching material designs and then using the Learning Management System (LMS) to support online lectures. After the RPS is updated and the teaching material design is prepared, both are then implemented with students and evaluated. The evaluation results show that the percentage of students correct in answering the questions given through the quiz was in the very good category with a percentage range of 81% - 100%. This supports that on average students are able to reach the very good category through the assessment indicators in the RPS as well as teaching materials that have been adapted to the independent learning curriculum.